International Approaches to Promoting Social and Emotional Learning in Schools A Framework for Developing Teaching Strategy (Taylor & Francis, 2022)
This book explores the importance of social and emotional learning (SEL) in schools to foster supportive environments and good relationships. It presents research from nine different countries with discussion of how teachers, teacher students and policy makers can ensure successful SEL at school. The book stresses the importance of social and emotional learning to allow students to become more autonomous and active in their own learning and also presents very innovative ways in learning and teaching the skills. It makes the case for understanding the processes of how SEL can develop and how it can work in different cultural contexts, considering different challenges of implementing SEL within the school context. The chapters draw on theoretical discussions illustrated by practical examples and explore the role of teacher training on SEL and how SEL can be applied within the school curriculum. Discussing an increasingly important topic in the field of education around the world, this book will be of great interest to academics, researchers, educational leaders, and university teacher trainers interested in developing social and emotional learning and overall well-being at school.
English
Keywords: Education; social and emotional learning; positive psychology; prevention; teacher training; school policy; curriculum development; SEL intervention; teacher in-house training; continuous training; teacher initial education; CPD